China-Japan rapprochement and the United States - Hattori, Ryūji, 1968- author.
1 online resource (184 pages).
Keywords: Based on extensive original research including interviews with key participants, this book examines how, following Richard Nixon's famous visit to China in 1972, Japan established formal diplomatic relations with China, doing so before the United States and other western countries. It considers the key personalities - prime minister Tanaka and foreign minister Ōhira on the Japanese side, and Zhou Enlai on the Chinese side, outlines how the discussions unfolded, and discusses the key issues which divided the two sides and how these issues were resolved: Japanese war reparations to China, how the two countries perceived their past, how Taiwan should be treated, and possession of the Senkaku Islands. The book also shows how Tanaka and Ōhira sought to reconcile China-Japanese relations with the US-Japan Security Treaty and to continue non-governmental exchanges with Taiwan following the severing of relations. Overall, the book emphasises that the nature of the relationship established in 1972 continues to be very important for understanding present day China-Japan relations.